Vietnamese and Korean: more alike than different - Đông, Lâm Quang (VNU Journal of Foreign Studies, 2013)
Abstract: Through a number of idiomatic expressions in Korean and Vietnamese, and based on the author’s knowledge and experience as an English speaker and teacher, the paper shares the author’s preliminary findings of the linguistic and cultural similarities of the two peoples, and gives additional support to the status of Konglish (Korean English) and Vinglish (Vietnamese English) as part of the Asian Englishes – the prideworthy varieties of the World’s Englishes to date. Keywords: idioms, proverbs, Konglish, Vinglish, Asian Englishes.